2014
DOI: 10.1111/gwat.12170
|View full text |Cite
|
Sign up to set email alerts
|

A Ternary Age‐Mixing Model to Explain Contaminant Occurrence in a Deep Supply Well

Abstract: The age distribution of water from a public-supply well in a deep alluvial aquifer was estimated and used to help explain arsenic variability in the water. The age distribution was computed using a ternary mixing model that combines three lumped parameter models of advection-dispersion transport of environmental tracers, which represent relatively recent recharge (post-1950s) containing volatile organic compounds (VOCs), old intermediate depth groundwater (about 6500 years) that was free of drinking-water cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Depth-specific samples and measurements of vertical flow rate before and after inflowing zones are combined in a mass balance to identify the concentration of inflowing groundwater. Collar and Mock (1997) appear to be the first to report this method, but it was subsequently adopted by the U.S. Geological Survey (Izbicki et al, 1999;Izbicki, 2004) and used to identify water quality issues (arsenic and salinity) in operational supply wells (Goldrath et al, 2015;Halford et al, 2010;Izbicki et al, 2005Izbicki et al, , 2006Izbicki et al, , 2008Izbicki et al, , 2010Jurgens et al, 2014;Landon et al, 2010;O'Leary et al, 2012O'Leary et al, , 2015Smith, 2005). Where such wells are regularly pumped at a high rate, the effect of ambient flows will be minimised, and inflows at all depths are likely to be groundwater native to the source interval.…”
Section: 1029/2019wr025713mentioning
confidence: 99%
“…Depth-specific samples and measurements of vertical flow rate before and after inflowing zones are combined in a mass balance to identify the concentration of inflowing groundwater. Collar and Mock (1997) appear to be the first to report this method, but it was subsequently adopted by the U.S. Geological Survey (Izbicki et al, 1999;Izbicki, 2004) and used to identify water quality issues (arsenic and salinity) in operational supply wells (Goldrath et al, 2015;Halford et al, 2010;Izbicki et al, 2005Izbicki et al, , 2006Izbicki et al, , 2008Izbicki et al, , 2010Jurgens et al, 2014;Landon et al, 2010;O'Leary et al, 2012O'Leary et al, , 2015Smith, 2005). Where such wells are regularly pumped at a high rate, the effect of ambient flows will be minimised, and inflows at all depths are likely to be groundwater native to the source interval.…”
Section: 1029/2019wr025713mentioning
confidence: 99%
“…There was no distinct difference in shapes of age PDFs between the upland and lowland wells (Figure ), despite the considerable difference in hydrogeological setting between the two regions. In this study, we did not use the DM for the perched groundwater samples because the model showed difficulty in deriving the fitting curves between the modelled and measured data within the acceptable error criteria (10%, Jurgens, Bexfield, & Eberts, ). The increased error could arise from the local degradation of CFCs in the perched aquifer system and subsequent decreases in CFC concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Where groundwater ages are deduced from measured concentrations of multiple environmental tracers, they often indicate mixtures of waters of different apparent ages (Bethke & Johnson, 2008;Cornaton & Perrochet, 2006;Ginn, 1999;Suckow, 2013;Varni & Carrera, 1998). Concentrations of environmental tracers that are indicative of relatively young waters (<60 years) and concentrations of tracers indicative of very old water have been found in the same groundwater samples at a wide range of field sites, as seen in Figure 1 (e.g., Alikhani et al, 2016;Arslan et al, 2015;Bretzler et al, 2011;Cook et al, 2005Cook et al, , 2017Corcho Alvarado et al, 2007;Genereux et al, 2009;Harrington, 2002;Jasechko et al, 2017;Jurgens et al, 2014Jurgens et al, , 2016Massoudieh et al, 2014;Samborska et al, 2013;Sültenfuβ et al, 2010;Talma et al, 2000). Cook et al (2005), for example, observed the presence of CFCs, an indicator of water less than 60 years old, in water with 14 C concentrations suggesting ages of thousands of years in a fractured rock aquifer.…”
Section: Introductionmentioning
confidence: 98%